2022
DOI: 10.3389/fpsyg.2022.924340
|View full text |Cite
|
Sign up to set email alerts
|

Effects of the COVID-19 Pandemic on the Success of Traditional Small and Medium Enterprises (SMEs): An Investigation of the Footprints of Economic Crisis Attributable to COVID-19

Abstract: The COVID-19 pandemic created a significant economic decline and altered market behavior, forcing buyers and dealers online. The traditional local market merchants are not fully equipped with e-commerce business techniques and strategies, which is a barrier to their e-commerce behavior and success. The study aims to help small-medium firms adapt to an uncertain economic environment instead of reducing or shutting down business-like in Pakistan. From health to education, economy to domestic and social protectio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 58 publications
0
1
0
Order By: Relevance
“…Eventually, improvement attempts made by firms are directed toward one sacred goal, which is enhancing the performance of the firm (Ployhart et al 2014;Bendickson and Chandler 2019;Javed et al 2023). However, COVID-19 has significantly affected employee performance in SMEs, and the degree of influence is greatly determined by the SMEs' absorptive capacity that is shaped by employees' learning propensity and their ability to apply what they have learned (Khaliq et al 2022). Moreover, Kwiotkowska and Gębczy ńska (2022) found that job characteristics in the post-pandemic period are crucial for determining the level of satisfaction and job success.…”
Section: Human Capital Development Programs (Hcdps) and Employee Perf...mentioning
confidence: 99%
“…Eventually, improvement attempts made by firms are directed toward one sacred goal, which is enhancing the performance of the firm (Ployhart et al 2014;Bendickson and Chandler 2019;Javed et al 2023). However, COVID-19 has significantly affected employee performance in SMEs, and the degree of influence is greatly determined by the SMEs' absorptive capacity that is shaped by employees' learning propensity and their ability to apply what they have learned (Khaliq et al 2022). Moreover, Kwiotkowska and Gębczy ńska (2022) found that job characteristics in the post-pandemic period are crucial for determining the level of satisfaction and job success.…”
Section: Human Capital Development Programs (Hcdps) and Employee Perf...mentioning
confidence: 99%